Correlations between the slip resistance and surface roughness of ceramic floor tiles (Research, Society and Development, 2021)
The characteristics of the floor surface profile are one of the factors that can be responsible for slip and fall accidents. To reduce the incidence of these accidents, it is essential to identify the profile features necessary for floor covering materials to be suitable for slipping risk areas. The objective of the present work was to investigate correlations between the slip resistance and the surface roughness of ceramic floor tiles. The slip resistance and the surface roughness of commercial ceramic tiles, with a diversity of surface finishes, were characterized by the pendulum method and contact profilometry, respectively. It was concluded that the presence of a large number of sharp peaks per unit of length of the profile is required for high slip resistance ceramic tiles. It was also found that the presence of waviness contributes to increasing the floors slip resistance even more. Through regression analysis, a good correlation between the pendulum results and the roughness parameter Ra was found.